2015
DOI: 10.4103/0972-5229.164800
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal mechanical ventilation: Indications and outcome

Abstract: Background and Aims:Decreasing mortality in sick and ventilated neonates is an endeavor of all neonatologists. To reduce the high mortality in this group of neonates, identification of risk factors is important. This study was undertaken to find out the indications of ventilation and complications in ventilated neonates and also study possible predictors of outcome.Subjects:Age <1-month; mechanically ventilated; not having suspected metabolic disorders or congenital anomalies; excluding postoperative patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 13 publications
3
19
0
Order By: Relevance
“…Neonatal sepsis (33.6%) was the commonest indication for ventilation followed by BA 24.3%, RDS 16%, apnea of prematurity 16% and MAS 10.1%. Similar pattern were reported in various other studies conducted within the country and abroad [8][9][10] . Shrestha P et al also reported that the 37.2% ventilated neonates had sepsis as the primary cause followed by respiratory distress (17.6%) Sepsis was the second most common cause for ventilation in studies conducted by Shrestha S et al, Srinivas N et al, Iqbal Qazi et al [8][9][10] Birth asphyxia was the most common cause for mechanical ventilation in neonates in BPKIHS Dharan (34%) and Paropakar Maternity and Women's Hospital (60%) Nepal.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Neonatal sepsis (33.6%) was the commonest indication for ventilation followed by BA 24.3%, RDS 16%, apnea of prematurity 16% and MAS 10.1%. Similar pattern were reported in various other studies conducted within the country and abroad [8][9][10] . Shrestha P et al also reported that the 37.2% ventilated neonates had sepsis as the primary cause followed by respiratory distress (17.6%) Sepsis was the second most common cause for ventilation in studies conducted by Shrestha S et al, Srinivas N et al, Iqbal Qazi et al [8][9][10] Birth asphyxia was the most common cause for mechanical ventilation in neonates in BPKIHS Dharan (34%) and Paropakar Maternity and Women's Hospital (60%) Nepal.…”
Section: Discussionsupporting
confidence: 91%
“…Sepsis had a uniformly poor outcome in other studies by Iqbal Q et al (35.3%) and Ananthraj A et al (46.1%). 10,14 Neonates with RDS had a survival rate of 36.8%, which is lower than 50 % -82.6 % as reported by other authors. 7,8,[10][11][12]17 Various authors claim that better survival rates in their study was made possible by early intervention and uniform use of surfactant in all PT/MAS/BA.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…3 Surfactant and mechanical ventilation are among the primary treatments to help infants with respiration. 4,5 Even after mechanical ventilation, infants show restlessness and stress because of abnormal and incomplete breathing, and this stress effectively results in altered lung function. 6 Some sedative drugs, such as benzodiazepines and opioids, are used to reduce infants' stress and restlessness under mechanical ventilation.…”
Section: Introductionmentioning
confidence: 99%